1998
DOI: 10.1103/physrevb.58.13442
|View full text |Cite
|
Sign up to set email alerts
|

Polarization dependence of anomalous x-ray scattering in orbital-ordered manganites

Abstract: In order to determine types of the orbital ordering in manganites, we study theoretically the polarization dependence of the anomalous x-ray scattering, which is caused by the anisotropy of the scattering factor. The general formula of the scattering intensity in the experimental optical system is derived and the atomic scattering factor is calculated in the microscopic electronic model. By using the results, the x-ray scattering intensity in several types of the orbital ordering is numerically calculated as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…This is contrary to a naive picture that the modulation is caused by the 3d states through the intra-atomic Coulomb interaction. 8,9 Subsequent theoretical studies on RXS in YVO 3 and YTiO 3 confirmed that the former picture is still valid. [10][11][12] RXS experiments on magnetic superlattice spots were carried out on several transition-metal compounds with antiferromagnetic ordering, such as RbMnF 3 (Ref.…”
Section: Introductionmentioning
confidence: 88%
“…This is contrary to a naive picture that the modulation is caused by the 3d states through the intra-atomic Coulomb interaction. 8,9 Subsequent theoretical studies on RXS in YVO 3 and YTiO 3 confirmed that the former picture is still valid. [10][11][12] RXS experiments on magnetic superlattice spots were carried out on several transition-metal compounds with antiferromagnetic ordering, such as RbMnF 3 (Ref.…”
Section: Introductionmentioning
confidence: 88%
“…As mentioned above, the unit cell of the orbital ordered phase has the dimensions ffiffi ffi 2 p a  2 ffiffi ffi 2 p a  c. As the origin of the anisotropy of the scattering factor, two mechanisms have been proposed; the Coulomb mechanism 21,22) and the JT mechanism. [24][25][26] In the former, the anisotropy of the form factor is attributable to the Coulomb interaction between 3d and 4p electrons.…”
Section: Structure Of the Orbital Ordermentioning
confidence: 99%
“…22) These structure factors are same as eqs. (1) and (2) when we substitute ðf x þ f y Þ=2 for f 3þ and É for 90 .…”
Section: Anisotropic Scattering Factor Tensor At 170 Kmentioning
confidence: 99%
“…22,34 The value of θ in the present calculation is about π. That is, the orbital wave functions are given by (|d 3z 2 −r 2 ± |d x 2 −y 2 )/ √ 2 where the electronic clouds are more elongated along the z direction in comparison with the d 3x 2 −r 2 and d 3y 2 −r 2 orbitals.…”
mentioning
confidence: 81%